Beetlejuice Beetlejuice [videorecording (DVD)] - Gough, Alfred, 1967-; Millar, Miles; Grahame-Smith, Seth; Keaton, Michael, 1951-; Ryder, Winona, 1971-; O'Hara, Catherine; Theroux, Justin; Bellucci, Monica, 1968-; Conti, Arthur, 2004-; Gorman, Burn, 1974-; Ortega, Jenna; Dafoe, Willem; et al. (Warner Bros. Entertainment Inc., 2024)
Beetlejuice is back! After an unexpected family tragedy, three generations of the Deetz family return home to Winter River. Still haunted by Beetlejuice, Lydia's life is turned upside down when her rebellious teenage daughter, Astrid, discovers the mysterious model of the town in the attic and the portal to the Afterlife is accidentally opened. With trouble brewing in both realms, it's only a matter of time until someone says Beetlejuice's name three times and the mischievous demon returns to unleash his very own brand of mayhem.